2016
DOI: 10.1016/j.immuni.2016.08.016
|View full text |Cite
|
Sign up to set email alerts
|

HIV Vaccine Design to Target Germline Precursors of Glycan-Dependent Broadly Neutralizing Antibodies

Abstract: SummaryBroadly neutralizing antibodies (bnAbs) against the N332 supersite of the HIV envelope (Env) trimer are the most common bnAbs induced during infection, making them promising leads for vaccine design. Wild-type Env glycoproteins lack detectable affinity for supersite-bnAb germline precursors and are therefore unsuitable immunogens to prime supersite-bnAb responses. We employed mammalian cell surface display to design stabilized Env trimers with affinity for germline-reverted precursors of PGT121-class su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
468
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 367 publications
(480 citation statements)
references
References 61 publications
10
468
1
1
Order By: Relevance
“…Following washing, plates were blocked with 3% BSA for 1 h at RT. The stabilized BG505 SOSIP construct MD39 22 was then captured at 2.5 μg/mL in PBS (50 μl/well) for 2 h at 37°C. Following washing, serially diluted antibodies in PBS/1% BSA were added for 30 min.…”
Section: Methods/supplementary Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Following washing, plates were blocked with 3% BSA for 1 h at RT. The stabilized BG505 SOSIP construct MD39 22 was then captured at 2.5 μg/mL in PBS (50 μl/well) for 2 h at 37°C. Following washing, serially diluted antibodies in PBS/1% BSA were added for 30 min.…”
Section: Methods/supplementary Informationmentioning
confidence: 99%
“…All 10 mAbs competed with VRC01-class antibodies on a stabilized BG505 SOSIP trimer termed MD39 (Fig. 3c) 22 . With the epitope specificity of NC-Cow1 identified, we next performed serum competition experiments with NC-Cow1 and found that the main serum specificity was to the CD4bs (Extended Data Table 2).…”
Section: Main Textmentioning
confidence: 99%
“…To address this problem, approaches for immunogen stabilization or grafting of immunogenic epitopes onto stable scaffolds have been implemented (15)(16)(17)(18)(19)(20)(21). However, key vaccine immunogens frequently have complex folds with significant flexibility and low stability.…”
mentioning
confidence: 99%
“…immunogen stabilization often require time-consuming and laborintensive cycles. For instance, in the design of superior HIV and respiratory syncytial virus immunogen variants, multiple rounds of rational design, random mutagenesis, and biochemical, immunological, and structural characterization were applied (15)(16)(17)(18)(19)(20)(21). Although effective, such iterative strategies limit the ability to respond quickly to emerging pathogens.…”
mentioning
confidence: 99%
“…Following the encouraging results of the VRC01 bnAb germline-targeting approach, a cell-surface mammalian display library platform was employed to select mutations within the BG505 SOSIP trimer backbone that would enable binding to iGL precursors of the PGT121-class of V3-N332 glycan-dependent bnAbs [36] (Figure 1C). Since bnAbs in this class use a long CDRH3 to bind the glycoprotein epitope at the base of the V3 loop and adjacent V1V2 loops, the authors created a glycan “hole” by removing specific glycans, altering variable loop lengths and substituting several residues within and around the epitope [12,36].…”
Section: Approaches To Design Immunogens Capable Of Inducing Hiv Bnabsmentioning
confidence: 99%